Patient safety features are more present in larger primary care practices - Gaal, Sander; Hombergh, Pieter van den; Verstappen, Wim; Wensing, Michel (Health policy, 2010)
Objectives: This study aimed to explore whether specific characteristics of a general practice organization were associated with aspects of patient safety management. Methods: Secondary analysis of data from 271 primary care practices, collected in 10 European countries. These data were collected by a practice visitor and physician questionnaires. For this study we constructed 10 measures of patient safety, covering 45 items as outcomes, and 6 measures of practice characteristics as possible predictors for patient safety. Results: Eight of the 10 patient safety measures yielded higher scores in larger practices (practices with more than 2 general practitioners). Medication safety (B 0.64), practice building safety (B 0.49) and incident reporting items (B 0.47) showed the strongest associations with practice size. Also measures on hygiene (B 0.37), medical record keeping (B 0.30), quality improvement (B 0.28), professional competence (B 0.24) and organized patient feedback items (B 0.24) had higher scores in larger practices. Conclusion: Larger general practice practices may have better safety management, although through our measurements no causal relationship could be established in this study.